The Efforts to Improve Environmental Behavior and Critical Thinking of Students through Guided Inquiry-Based Learning on Environmental Education-Based Science - Muhlisin, Muhlisin; Rosiana, Ida; Rahayuningsih, Yunia; Suharyana, Yana (Jurnal Penelitian dan Pembelajaran IPA, 2019)
This study aimed to determine the influence of guided inquiry-based learning toward the improvement of environmental behavior and critical thinking of students in environmental education-based science. This study used the Classroom Action Research method through two cycles each consisting of planning, action, observation, and reflection. The objects of this study were 35 students of the 3rd class of Junior High School of SMPIT Raudatul Jannah in Cilegon, Indonesia. The results showed that on the first cycle it has no a significant change in environmental behavior and critical thinking competence of students but then an increase in the second cycle. In general, it can be concluded that guided inquiry learning in science can increase environmental behavior and critical thinking of students